2012
DOI: 10.1038/mp.2012.95
|View full text |Cite
|
Sign up to set email alerts
|

Different changes in cortical tumor necrosis factor-α-related pathways in schizophrenia and mood disorders

Abstract: The growing body of evidence implicating tumor necrosis factor-α (TNFα) in the pathophysiology of psychiatric disorders led us to measure levels of that protein in the cortex of subjects with major depressive disorders (MDD). Having reported an increase (458%) in the levels of the transmembrane (tmTNFα), but not the soluble (sTNFα), form of the protein in Brodmann's area (BA) 46, but not 24, in people with the disorder, we decided to examine additional components of TNFα-related pathways in the same regions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 69 publications
1
73
1
Order By: Relevance
“…38,[49][50][51][52][53] A previous study from our group reported increased expres sion of IL4 and IL13, and no differences in IL6, TNFα and IL1β, in the orbitofrontal cortex of individuals who died by suicide compared with controls. 38 This variability in the ex pression of certain cytokines in the brain suggests that cau tion is indicated regarding their use as biological markers of mood disorders.…”
Section: Discussionmentioning
confidence: 62%
“…38,[49][50][51][52][53] A previous study from our group reported increased expres sion of IL4 and IL13, and no differences in IL6, TNFα and IL1β, in the orbitofrontal cortex of individuals who died by suicide compared with controls. 38 This variability in the ex pression of certain cytokines in the brain suggests that cau tion is indicated regarding their use as biological markers of mood disorders.…”
Section: Discussionmentioning
confidence: 62%
“…The tmTNF␣ levels were increased in the postmortem anterior cingulate of bipolar disorder patients [67]. The TNFR2 mRNA level was significantly decreased in the dorsolateral prefrontal cortices of bipolar and major depressive disorder patients [67].…”
Section: Bipolar Disordermentioning
confidence: 95%
“…The tmTNF␣ levels were increased in the postmortem anterior cingulate of bipolar disorder patients [67]. The TNFR2 mRNA level was significantly decreased in the dorsolateral prefrontal cortices of bipolar and major depressive disorder patients [67]. The nuclear protein and mRNA levels of microglial NFKB1 (p50) and NF-Bp65 [40] were significantly increased in the postmortem frontal cortices of bipolar disorder patients.…”
Section: Bipolar Disordermentioning
confidence: 98%
See 2 more Smart Citations